DIGITAL ECONOMY TRANSFORMATION IN INCREASING GREEN ECONOMIC DEVELOPMENT IN INDONESIAN TOWARDS SUSTAINABLE DEVELOPMENT - Febriza, Milla; Monica, Mutiara; Rozalinda, (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
Advances in digital technology affect various sectors, including the economic sector with the presence of the digital economy, so that the digital economy is expected to help in the implementation of the green economy and support the achievement of Sustainable Development Goals. The purpose of this study is to analyze how the effects of digital transformation in the development of a green economy in Indonesia and support the achievement of sustainable development goals. This research is a qualitative Systematic Literature Review (SLR) using the Prisma model. The data sources in this study come from scopus indexed articles for the last 10 years, starting from 2015 to 2024. The data collection technique in this study used Publish or Perish software. The data analysis technique uses the Prisma model which is presented in a flow diagram. The results showed that based on previous research related to the digital economy and green economy, it was found that the digital economy is able to encourage the development of the green economy and can help achieve sustainable development goals by utilizing the development of digitalization technology to the fullest.